Evolution & Development of Islamic Banking – The Case of Pakistan - Muhammad Aqib Ali (European Journal of Islamic Finance, 2014)
The paper attempts to explore the roots of Islamic Banking in the world in general and in Pakistan in particular to assess the evolution and development/growth of Islamic Banking worldwide and especially in Pakistan. The paper highlights the chronology of Islamic Banking globally and in Pakistan and also traces the progress of Islamic Banking internationally with special reference to Pakistan. The facts reflect an encouraging global Islamic Banking outlook. The findings also show that the progress of Islamic Banking in Pakistan has been consistent and quite encouraging. As the time passed the quantum of Islamic Banking in the country expanded and is continuing to move in the right direction. From a new initiative in the 1970s, Islamic Banking is now a force to reckon with, the annual growth rate of more than 16% proves this fact.